A transcriptome-based global map of signaling pathways in the ovarian cancer microenvironment associated with clinical outcome. Issue 1 (December 2016) - Reinartz, Silke; Finkernagel, Florian; Adhikary, Till; Rohnalter, Verena; Schumann, Tim; Schober, Yvonne; Nockher, W.; Nist, Andrea; Stiewe, Thorsten; Jansen, Julia; Wagner, Uwe; Müller-Brüsselbach, Sabine; et al.
Abstract Background Soluble protein and lipid mediators play essential roles in the tumor environment, but their cellular origins, targets, and clinical relevance are only partially known. We have addressed this question for the most abundant cell types in human ovarian carcinoma ascites, namely tumor cells and tumor-associated macrophages. Results Transcriptome-derived datasets were adjusted for errors caused by contaminating cell types by an algorithm using expression data derived from pure cell types as references. These data were utilized to construct a network of autocrine and paracrine signaling pathways comprising 358 common and 58 patient-specific signaling mediators and their receptors. RNA sequencing based predictions were confirmed for several proteins and lipid mediators. Published expression microarray results for 1018 patients were used to establish clinical correlations for a number of components with distinct cellular origins and target cells. Clear associations with early relapse were found for STAT3-inducing cytokines, specific components of WNT and fibroblast growth factor signaling, ephrin and semaphorin axon guidance molecules, and TGFβ/BMP-triggered pathways. An association with early relapse was also observed for secretory macrophage-derived phospholipase PLA2 G7, its product arachidonic acid (AA) and signaling pathways controlled by the AA metabolites PGE2, PGI2, and LTB4 . By contrast, the genes encoding norrin and its receptor frizzled 4, both selectively expressed by cancer cells and previously not linked to tumor suppression, show a striking association with a favorable clinical course. Conclusions We have established a signaling network operating in the ovarian cancer microenvironment with previously unidentified pathways and have defined clinically relevant components within this network.